Current developments in chemical recycling of post-consumer polyethylene terephthalate wastes for new materials production: A review. (10th July 2019) - Raheem, Ademola Bolanle; Noor, Zainura Zainon; Hassan, Azman; Abd Hamid, Mohd Kamaruddin; Samsudin, Sani Amril; Sabeen, Ali Hussein
Abstract: This paper appraised divergent chemical depolymerization routes for reprocessing chemically synthesis polyethylene terephthalate (PET) plastics bottle waste and offer resolutions to control the environmental complications emanating attributable to its utilize and disposal to the habitat. The consciousness to prune environs contaminants and make it "green" demand for the reclaim and reprocessing it back to PET bottles, precursor products like glycolyzate, and other inventions such as unsaturated polyester resins, epoxy resins, composites etc. Controlling this necessitates assorted reprocessing methods of which chemical recycling that transform PET into monomer/oligomer is the most prosperous one. This review explored in detail current events in the PET chemical recycling using glycolysis method. The study was based on their current evolution concerning their depolymerization agents, reaction conditions, kinetics of reactions, catalysts used, products of reprocessing, and their prospective use. Benefits of PET recycling and glycolysis as well as criteria and necessitation factors that used to adjudge them as the best method and sub-method respectively were highlighted. The prospect for the conversion of glycolyzate into other PET recycling methods products were shown. PET recycling was concluded to be a partial resolution to wastes management, and also grants the conservation of natural petrochemical resources and energy.